PERFORMANCE APPRAISAL: A PHENOMENOLOGICAL STUDY IN INDONESIAN ISLAMIC HIGHER EDUCATION INSTITUTION - Yayan Firmansah (Value : Jurnal Manajemen dan Akuntansi, 2023)
Given adequate studies on performance appraisal, there is still a lack of study regarding how the performance appraisal is conducted in Islamic higher education institutions, particularly in Indonesia as the biggest Muslim country in the world. With regard to this, the current study aims to explore the lived experience of line managers in Islamic higher education institutions in conducting performance appraisal. By doing so, this study could be the foundation of Islamic higher education institutions in identifying and revealing the current situation regarding the qualities of its people. The current study is a qualitative study with phenomenology as its approach. Data were collected using semi-structured with the sample of the study, which is heads of department since they are the main actor in performance appraisal activities. As the result, this study found four themes related to the lived experiences of department heads in Islamic university in conducting performance appraisal, namely main aspects evaluated, the determinant factors of performance appraisal, benefit obtained and obstacle encountered. Theoretical and practical implications, as well as suggestions for future studies are discussed. Keywords: performance appraisal, Islamic university, lived experience, phenomenology